2009
DOI: 10.1080/09286580902999397
|View full text |Cite
|
Sign up to set email alerts
|

Visual Function Versus Visual Acuity in Older People

Abstract: VF impairment is common in older persons and when associated with other limitations, it may be considered a major health problem with important consequences. As a complement to the preventive care guidelines on VA in older persons, assessment of VF impairment in clinical practice, using appropriate visual screening tools, is advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…33 A recent population-based, retrospective cohort study 34 in an older population in Quebec, Canada, found that clinically diagnosed vision impairment independently increased the risk of depression (hazard ratio, 1.35 [95% CI, 1.10–1.66] for severe cases; hazard ratio, 1.35 [95% CI, 1.09–1.69] for moderate visual impairment). Other studies 2,37,41,60 also found that visual acuity loss and depressive symptoms were independently associated with visual function status in people 65 years of age or older.…”
Section: Vision Loss and Depressionmentioning
confidence: 81%
“…33 A recent population-based, retrospective cohort study 34 in an older population in Quebec, Canada, found that clinically diagnosed vision impairment independently increased the risk of depression (hazard ratio, 1.35 [95% CI, 1.10–1.66] for severe cases; hazard ratio, 1.35 [95% CI, 1.09–1.69] for moderate visual impairment). Other studies 2,37,41,60 also found that visual acuity loss and depressive symptoms were independently associated with visual function status in people 65 years of age or older.…”
Section: Vision Loss and Depressionmentioning
confidence: 81%
“…Later assessments of self-rated functional vision were proposed to be useful for vision screening of community-dwelling older adults (Valbuena et al 1999) and for assessing their risk of falling (Kamel et al 2000). Thus far, however, the relationship between self-rated functional vision and physical functioning has not been evaluated using well established physical performance tests (Hidalgo et al 2009). The aim of this crosssectional study was to investigate whether there is a relationship between self-rated functional vision and objective measures of balance and mobility among older adults living in community.…”
Section: Introductionmentioning
confidence: 99%
“…However this is in line with existing literature, for example reported a prevalence of self reported fair and poor vision of 10% in people aged between 40 and 69 was reported (Klein et al 1999), while the prevalence increased over 70 years of age. Hidalgo et al (2009) report a prevalence of 6% (bad or very bad vision by self report) in participants age 65 and older. Although the current study confirms a relationship between visual acuity and SRV, additional factors including the presence of ocular pathology and reduced visual processing capacity are identified as important determinants of SRV.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have investigated intelligence (Kempen et al 1996) and global cognitive status (Hidalgo et al 2009) but their results are limited by the impossibility to control for a range of confounding factors.…”
Section: Introductionmentioning
confidence: 99%